2014
DOI: 10.5530/pc.2014.3.3
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Jacaranda (Bignoniaceae): An Updated Review

Abstract: Genus Jacaranda has been traditionally used in treating skin disorders, venereal diseases, leishmaniasis, colds and rheumatism. Additionally, some species have shown diuretic and astringent properties. Objective: This review highlights and updates the traditional uses, pharmacology and phytochemistry of the genus Jacaranda. Materials and Methods: Information was obtained from Google Scholar, Scirus, PubMed and ScienceDirect. Results: Phytochemical studies on Jacaranda species have shown the presence flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Different classes of phytochemicals have been identified in Jacaranda species, and the main metabolites described are sterols, triterpenes, fatty acids, flavonoids, phenylpropanoids, phenylethanoids and quinones (Mostafa et al 2014). For instance, a recent study with extracts from Jacaranda caroba leaves identified thirteen phenolic compounds (Ferreres et al 2013) while four acidic triterpenes were isolated from Jacaranda puberula leaves (De Almeida et al 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Different classes of phytochemicals have been identified in Jacaranda species, and the main metabolites described are sterols, triterpenes, fatty acids, flavonoids, phenylpropanoids, phenylethanoids and quinones (Mostafa et al 2014). For instance, a recent study with extracts from Jacaranda caroba leaves identified thirteen phenolic compounds (Ferreres et al 2013) while four acidic triterpenes were isolated from Jacaranda puberula leaves (De Almeida et al 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Pharmacognosy is a developing science that started by dealing with morphology and taxonomy of crude drugs, then it focused on isolation, quantification and structure elucidation of active compounds [7][8][9], these phytochemicals may have potential protective or disease preventive properties [10,11], essential oils characterization [12][13][14], and recently the term Reverse Pharmacognosy has evolved by concerning with the potential biological activity of a crude drug or its isolated compounds. This can result in the discovery of novel lead compounds or new biological activities [7,15].…”
Section: Introductionmentioning
confidence: 99%
“…This way, the genus Jacaranda is of a particular interest: it includes 49 species of trees and shrubs, native from the Neotropical region. Several species have been introduced to Africa, Asia and Oceania and successfully cultivated, often as ornamental trees, and some of them eventually naturalized (Mostafa et al 2014). While morphological observations of the arboreal species have shown simply root systems, some shrubby species have disclosed more complex subterranean systems, such as xylopodium and soboles: for instance, one individual of Jacaranda decurrens of more than one thousand years of life was identified, with a large and dense ramification of the soboles (Oliveira et al 2003, Alves et al 2013.…”
Section: Introductionmentioning
confidence: 99%